Assessment of sustainability progress indicators in the wine industry - DIACONU, Cristina (Journal of Social Sciences)
In the context of climate change, wine businesses face the challenge of adapting their business models to promote sustainable development. This requires a careful balance between the economic, social and environmental dimensions of their activities. To measure progress towards sustainability in the wine sector, it is crucial to develop a set of comprehensive indicators. This study aims to analyze sustainability indicators within the wine industry, as presented in current literature and existing research. The study highlights the importance of effective management of waste and by-products in winemaking to reduce environmental impact and create new economic opportunities. It presents a set of indicators for monitoring environmental, economic, and social dimensions of sustainability, emphasizing the need for a balanced approach to ensure the viability and progress of the sector.